The Impact of Global English on English Language Teaching (ELT) Methodologies in Non-native Contexts - Mathavan, N.; Anestine, A.B. (University of Jaffna, 2025)
The growth of English in second and foreign language contexts has considerably impacted English Language Teaching (ELT). As an international language, English has transformed from an academic subject to a practical medium of communication. The change has encouraged educators to reconsider the curriculum design, teaching methodologies and instructional frameworks (Seidlhofer,2011). The research examined the influence of English in non-native contexts with a focus on curriculum adaptation, teacher development and student learning outcomes. The research’s primary finding is the shift from conventional grammar-based training to Communicative and Task-based approaches. Task-based approaches reflect the fundamental needs of English in international contexts (Richards & Rodgers, 2014). The study further examined how the integration of English Language and local varieties challenges native speaker norms while promoting inclusive and context-sensitive instruction. In addition, the study identified the significance of digital tools, such as virtual learning platforms and AI-powered resources, in shaping the teaching and learning experiences in different settings. The study followed a qualitative research methodology. It conducted surveys and interviews with English teachers and learners in Sri Lanka. The results showed how globalization has introduced diverse linguistic and cultural perspectives and expanded ELT teaching methods. However, the study also points to the challenges, such as insufficient teacher training, lack of adequate digital resources, and reluctance to adopt contextualized teaching approaches regarding ELT. The study recommends an adaptable and contextualized ELT paradigm that connects global English proficiency to local language and cultural realities. These findings will help shape discussions concerning ELT’s future in a non-native environment. It will also assist teaching techniques that recognize the diversity and evolution of English in a global context.
Keywords: Global English; Non-native contexts; ELT methodologies; Digital learning; Task-based and Communicative Approach